Investigating nano-precipitation in a V-containing HSLA steel using small angle neutron scattering. (15th February 2018) - Wang, Y.Q.; Clark, S.J.; Janik, V.; Heenan, R.K.; Venero, D. Alba; Yan, K.; McCartney, D.G.; Sridhar, S.; Lee, P.D.
Abstract: Interphase precipitation (IPP) of nanoscale carbides in a vanadium-containing high-strength low-alloy steel has been investigated. Small angle neutron scattering (SANS) and transmission electron microscopy (TEM) were employed to characterize the precipitates and their size distributions in Fe-0.047C-0.2V-1.6Mn (in wt.%) alloy samples which had been austenitized, isothermally transformed at 700 °C for between 3 and 600 min and water quenched. TEM confirms that, following heat treatment, rows of vanadium-containing nanoscale interphase precipitates were present. Model-independent analysis of the nuclear SANS signal and model fitting calculations, using oblate spheroid and disc-shapes, were performed. The major axis diameter increased from 18 nm after 3 min to 35 nm after 600 min. Precipitate volume percent increased from 0.09 to 0.22 vol% over the same period and number density fell from 2 × 10 21 to 5 × 10 20  m −3 . A limited number of measurements of precipitate maximum diameters from TEM images showed the mean value increased from 8 nm after 5 min to 28 nm after 600 min which is in reasonable agreement with the SANS data. Graphical abstract: Image 1